KUALITAS DAN KESUBURAN AIR BUDIDAYA LELE DUMBO (Clarias gariepinus) DENGAN VOLUME PERGANTIAN AIR BERBEDA - Bambang Triyatmo (Universitas Gadjah Mada, 2002)
Study was conducted to evaluate the quality and productivity of water used during two period catfish culture for 5 months. Catfish fries were cultured in fiberglass containers for two and three months without draining. During 5 months, 0, 5, 10, 20 or 40 percent of total water volume were replaced daily. The quality and productivity of water were observed every months.Results indicated that the decrease of water qualities were more notebly when the water replacement in the culture system was carried out in less portion. However, the less portion of the water replacement made higher water fertility for the growth of phytoplankton.